AcGI1, a novel genomic island carrying antibiotic resistance integron In687 in multidrug resistant Achromobacter xylosoxidans in a teaching hospital in Thailand. Issue 14 (27th June 2020) - Pongchaikul, Pisut; Santanirand, Pitak; Antonyuk, Svetlana; Winstanley, Craig; Darby, Alistair C
ABSTRACT: This study investigated the genetic basis of multidrug resistance in two strains of Achromobacter xylosoxidans isolated from patients attending a hospital in Thailand in 2012. These isolates were highly resistant to cephalosporins, aminoglycosides, fluoroquinolones, co-trimoxazole and carbapenems. Whole genome sequencing revealed that the two isolates were not clonally related and identified a carbapenem resistance gene-habouring integron (In687), residing in a novel genomic island, AcGI1. This In687 shares 100% identical nucleotide sequence with ones found in Acinetobacter baumannii Aci 16, isolated from the same hospital in 2007. We report the first analysis of multidrug-resistant A. xylosoxidans isolated in Thailand, and the first example of this island in A. xylosoxidans . Our data support the idea that resistance has spread in Thailand via horizontal gene transfer between species and suggest the possibility of A. xylosoxidans may serve as a reservoir of antibiotic resistance, especially in hospital setting. Abstract : The first identification of a novel genomic island, AcGI1, containing multiple antimicrobial resistance genes in A. xylosoxidans .